On the issue of shielding properties of plasma in the outside separatrix region of U-3M - Konovalov, V.G.; Chechkin, V.V.; Ggrigor’eva, L.I.; Shapoval, A.N. (Вопросы атомной науки и техники, 2014)
When providing experiments on RF plasma production and heating in U-3M torsatron there was observed sudden decrease (up to two times) of mean confined plasma density during step-rise of an RF antenna voltage. Trying to analyze the reason of this effect we estimated a screening effect of the out-separatix plasma, characteristics of which were recently measured. It was found that at the plasma confinement border the attenuation is: 6 % for H2, 1.4, 7, 6 % for C, Fe and Ti atoms correspondingly. This is much below the result of attenuation (~70 %) estimated in [1] for the flux of laser ablated C atoms. При проведении экспериментов на торсатроне У-3M при ВЧ-способе создания и нагрева плазмы наблюдалось неожиданное уменьшение (примерно двукратное) средней плотности удерживаемой плазмы при ступенчатом нарастании напряжения на ВЧ-антенне. Пытаясь установить причину этого явления, мы оценили экранирующую роль засепаратрисной области плазмы по результатам недавно проведенных измерений. Было установлено, что на границе удерживаемой плазмы ослабление потока составляет: 6 % для Н2, 1.4, 7, 6 % для C, Fe, Ti соответственно. Это значительно ниже степени ослабления (~70 %), полученной в работе [1] для потока атомов С при лазерной абляции графитовой мишени. При проведенні експериментів на торсатроні У-3М при ВЧ-способі створення та нагріву плазми спостерігалося несподіване зменшення (приблизно дворазове) середньої густини утримуваної плазми при ступінчастому наростанні напруги на ВЧ-антені. Намагаючись встановити причину цього явища, ми оцінили екрануючу роль засепаратрисної області плазми за результатами недавно проведених вимірювань. Було встановлено, що на межі утримуваної плазми ослаблення потоку становить: 6 % для Н2, 1,4, 7, 6 % для C, Fe, Ti відповідно. Це значно нижче ступеня ослаблення (~ 70 %), отриманого в роботі [1] для потоку атомів С при лазерній абляції графітової мішені.